Morphological Description of Some Megachilidae Species in Aljabal Alakhder, Libya - Almabrouk, Marwah Y. H.; Bataw, Ali A.; Attia, Mansour S. A.; Mohammrd, Asrana R.; Algbali, Muna M (Al-Mukhtar Journal of Sciences, 2022)
Bees are a large and diverse species of insects belonging to the Hymenoptera order. The family Megachilidae represents a large part of most of the bee fauna all over the world as a result of their importance as pollinators. The study aimed to describe the morphological characteristics of three species of wild bees belonging to Megachile parientina (Geoffroy, 1785), Rhodanthidium sticticum (Fabricius, 1787), and Anthidium diadema Latreille, 1809 in Aljabal Alakder, Libya. Specimens were collected by hand net from different locations in the Aljabal Alakder area (Albayda and Alwastia). The morphological characters were described by using the OPTIC microscope. Measurements were taken at full body length (in cm), front wings length, thorax and abdomen width, body color was taken (head, abdomen, thorax, wings), and the study described in details the morphology of mouthparts, wings venation, antenna and abdominal structure for all species. The morphological structures vary between the different species in color, size, and wings. The body length of M. parientina was 19 mm, R. sticticum was 12 mm, and A. diadema was 13 mm. The study’s conclusion insists on the importance of morphological description studies to facilitate the identification of wild bees species in Libya.